1996
DOI: 10.1063/1.472265
|View full text |Cite
|
Sign up to set email alerts
|

A molecular beam optical/Stark study of calcium monomethyl

Abstract: A molecular beam optical/Stark study of calcium monoacetylideOptical and optical Stark spectra of the 0 0 0 Ã 2 E-X 2 A 1 band system of a supersonic molecular beam sample of calcium monomethyl, CaCH 3 , have been recorded. Field free spectroscopic parameters were obtained on fitting the ͉͑K R Ј ͉ ϭ 1, ͉KЈ͉ϭ0 and 2͒-(͉K R Љ͉ ϭ 1) and the ͉͑K R Ј ͉ ϭ 0, ͉KЈ͉ϭ1͒-(͉K R Љ͉ ϭ 0) subbands. The branch features were reassigned and a resulting new set of spectroscopic parameters determined. The value of the a-principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Experimental evidence is also found in work by Whitham et al (13), who showed in their paper concerning the B-X system of CaOCH 3 , that the experimental value of the spin rotation constant, ε bb , for the B state differs from the calculated pure precession value by ∼25%. Finally, the spinrotation constants ε aa = 3.6(9)10 −3 cm −1 and ε bc = 3.2(8) × 10 −3 cm −1 are very close and both positive, as was the case in CaCH 3 (11) .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Experimental evidence is also found in work by Whitham et al (13), who showed in their paper concerning the B-X system of CaOCH 3 , that the experimental value of the spin rotation constant, ε bb , for the B state differs from the calculated pure precession value by ∼25%. Finally, the spinrotation constants ε aa = 3.6(9)10 −3 cm −1 and ε bc = 3.2(8) × 10 −3 cm −1 are very close and both positive, as was the case in CaCH 3 (11) .…”
Section: Discussionmentioning
confidence: 63%
“…Calcium species have drawn particular attention: CaOH should be abundant in circumstellar envelopes (7) and the question of its electric dipole moment has been the subject of both experimental (8) and theoretical (9) investigations. Marked similarities between spectra of linear CaOH and the Ca monohalides invited extension of these studies to CaR compounds of lower symmetries, in order to understand their electronic structure and bonding: for instance CaNH 2 (10) for C 2v , CaCH 3 (11) and CaOCH 3 (12,13) for C 3v . The C 3v species are of particular interest for Jahn-Teller studies, as shown in a recent review (14), because they give access to degenerate E electronic states where such vibronic interaction can take place.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the values for e aa in CaCH 3 [26] and CaOCH 3 [27] in the à 2 E state are very small, even smaller than for MgCH 3 (see above). This tells us that the Jahn-Teller interaction in these molecules is vanishingly small, in disagreement with the assignments reported in [28] and [9].…”
Section: Discussionmentioning
confidence: 69%
“…We recall that a knowledge of the parameter d t allows the expectation value of the orbital angular momentum L z to be calculated, using Eq. (26). Because the linear Jahn-Teller operator for a C 3v (or D 3h ) molecule causes a simultaneous change in K and l of ±2 and ±1, respectively, knowledge of d t also allows the expectation value Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation